Water, Sanitation and Hygiene : Interventions and Diarrhoea - Fewtrell, Lorna (World Bank, Washington, DC, 2013)
Many individual studies have reported results of interventions intended to reduce illness through improvements in drinking water, sanitation facilities and hygiene practices. This paper provides a formal systematic review and meta-analysis examining the evidence of the effectiveness of these interventions. Through a comprehensive literature search and bibliographic review, 2120 titles published prior to June 26th, 2003 were screened, 336 papers were obtained for a more thorough examination, and 64 of these papers (representing 60 distinct studies) were identified which detailed water supply, water quality, sanitation, hygiene or multifactorial interventions and examined diarrhoea morbidity as a health outcome in non-outbreak conditions. Data were extracted from these papers and pooled through meta-analysis to provide summary estimates of the effectiveness of each type of intervention. All interventions reduced diarrhoea morbidity, with pooled risk ratios ranging from 0.98 to 0.51 (where a risk ratio of 1.0 indicates no effect and lower risk ratios indicate stronger effects). The removal of poor quality studies from the analyses improved the strength of the intervention impact in most cases. The 95 percent confidence intervals (CIs) for the pooled risk ratios of various interventions overlapped, indicating their effects were not statistically significantly different from each other.